Local knowledge as a foundation for environmental peacebuilding: Interpreting Johan Galtung’s theory within the environmental security framework - Ingrida, Nadia Varayandita (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Environmental degradation and social inequality demonstrate that peace cannot be defined simply as the absence of war or the cessation of conflict. This paper draws on the peace theory proposed by Johan Galtung. In this context, positive peace is understood as an effort to transform structural conditions that maintain inequality, by linking environmental justice to human dignity and ecological ethics. Methods: Using a qualitative-interpretive approach with conceptual analysis of various literature and secondary data through reports from international institutions, news, and academic journals related to environmental security issues and local community-based studies, including indigenous peoples affected by environmental change. The analysis was conducted through a synthesis of Johan Galtung's peace theory with the human security framework as developed by the UNDP in 1994, specifically on the environmental security dimension and its relationship with local knowledge systems. Findings: The analysis shows that local knowledge strengthens environmental security through adaptive and relational mechanisms that maintain the balance between humans and nature. Thus, local knowledge is not merely a traditional practice, but a foundation for sustainable peace that restores human dignity and its ecosystem. This role is evident in the three main dimensions of human security; freedom from fear, freedom from want, and freedom to live in dignity—interpreted as ecological rights within a reciprocal human-nature relationship. Conclusion: The integration of positive peace and human security in environmental security offers a transformative approach to environmental peacebuilding that places local knowledge in collaboration in determining policy directions and nonviolent resistance in ecological restoration. Novelty/Originality of this article: The novelty of this research contributes to bridging Johan Galtung's theory of peace and environmental security to the discourse of environmental peacebuilding through the lens of local knowledge epistemology, by offering a conceptual framework that places local knowledge as a core element in sustainable peacebuilding.